Chaetomitrium Ciliatum - Monica Suleiman; Hiroyuki Akiyama (Museum of Nature and Human Activities, 2014)
(1) Plants are sparsely branched, somewhat flattened; (2) branch leaves are deeply concave, plicate, and constricted below apices; (3) leaf margins are spinose-serrate above and denticulate below with simple erect teeth; (4) costae are strong, reaching 1/3 of leaf length; (5) laminal cells are thin-walled, slightly porose, laxly spinoseprorate above, prorulate below; (6) setae (immature) are setulose but smooth at the extreme base; (7) capsules are inclined and smooth; (8) calyptrae are cucullate, densely hispid all over the surface, with short hairs at the base.